1999
DOI: 10.1063/1.873645
|View full text |Cite
|
Sign up to set email alerts
|

Dust-acoustic solitary waves and double layers in dusty plasma with variable dust charge and two-temperature ions

Abstract: With two-temperature ions in dusty plasma, the effects of variable dust charge on small-amplitude dust-acoustic solitons and large-amplitude dust-acoustic solitary waves are investigated. It is found that both compressive and rarefactive solitons (and solitary waves), as well as double layers, exist. The introduced small, but finite, number density of the lower temperature ions provides the possibility of the coexistence of large-amplitude rarefactive with compressive dust-density solitary waves. The amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 14 publications
3
89
0
Order By: Relevance
“…It was found that both compressive and rarefactive solitary waves as well as compressive and rarefactive double layers exist. The small and large amplitudes DASWs in a dusty plasma with variable dust charge and two-temperature ions are investigated (Xie et al 1999). They examined a necessary condition that must be satisfied to achieve the validity of the two-temperature ions assumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that both compressive and rarefactive solitary waves as well as compressive and rarefactive double layers exist. The small and large amplitudes DASWs in a dusty plasma with variable dust charge and two-temperature ions are investigated (Xie et al 1999). They examined a necessary condition that must be satisfied to achieve the validity of the two-temperature ions assumption.…”
mentioning
confidence: 99%
“…For a head-on collision between two solitary waves, we must search for the evolution of solitary waves propagating in opposite directions, and hence we need to employ a suitable asymptotic expansion to solve the original fluid dynamics equations. Using the extended Poincaré-Lighthill-Kuo (PLK) method (Guoxiang Huang and Velarde 1996), for example, the head-on collision between DASWs in an unmagnetized (Xue 2004) and a magnetized (Xue 2006) dusty plasma is studied. The author of this reference found that the dust charge variation, the magnitude and the obliqueness of the external magnetic field significantly modify the phase shifts.…”
mentioning
confidence: 99%
“…This means that generally a rarefactive soliton is appeared in the medium. Consequently amplitude of the solitary waves is smaller as compared to the onedimensional case [16].…”
Section: Conclusion and Remarkmentioning
confidence: 97%
“…where Φ denotes the dust particle surface potential related to the plasma potential φ [12] and z d is the normalized dust charge obtained from:…”
Section: Mathematical Analysismentioning
confidence: 99%
“…Brindaban Das and Prasanta Chatterjee [11] studied large amplitude double layers in dusty plasma with non-thermal electrons and two temperature isothermal ions. Xie et al [12] investigated the small-and largeamplitude dust-acoustic solitary waves (DASWs) in dusty plasmas with variable dust charge and two-temperature ions. It was noticed that both compressive and rarefactive solitary waves as well as double layers exist.…”
Section: Introductionmentioning
confidence: 99%